Conference address by YBhg President/Vice-Chancellor OUM, Prof Tan Sri Anuwar Ali at National Institute of Accountants Conference - Anuwar Ali, (Open University Malaysia (OUM), 2006)
Speech of the President/Vice-Chancellor OUM, Prof Tan Sri Anuwar Ali at National Institute of Accountants Conference.